OP64 The impact of political economy on population health: a systematic review of reviews. (3rd September 2019) - McCartney, G; Hearty, W; Arnot, J; Popham, F; Cumbers, A; McMaster, R
Abstract : Background: Although there are many studies considering specific aspects of political economy and health, there have been few attempts to synthesise the literature. This work describes a systematic review of reviews of the literature describing the impact of political economy on population health. Methods: We searched Medline, Embase, International Bibliography of the Social Sciences (IBSS), Proquest Public Health, Sociological Abstracts, Applied Social Sciences Index and Abstracts (ASSIA), EconLit, SocIndex, Web of Science and the grey literature via 'Google Scholar'; for reviews of the literature. Relevant exposures were differences or changes in: policy, law or rules; economic conditions; institutions or social structures; politics, power or conflict. Relevant outcomes were any overall measure of population health such as self-assessed health, mortality, life expectancy, survival, morbidity, well-being, illness, ill-health and lifespan. All citations were reviewed independently by two authors for relevance. Critical appraisal of all included reviews was undertaken using modified AMSTAR criteria and then synthesised narratively giving greater weight to the higher quality reviews. Results: From 4, 912 citations, 58 reviews were included. Both the quality of the reviews and the underlying studies within the reviews were variable. Social democratic welfare states, higher public spending, fair trade policies, extensions to compulsory education provision, microfinance initiatives in low income countries, health and safety policy, improved access to healthcare, and high quality affordable housing have positive impacts on population health. Neoliberal restructuring seems to be associated with increased health inequalities and higher income inequality with lower self-rated health and higher mortality. There are evidence gaps on the relationship between governance, polities, power, macroeconomic policy, public policy and population health, including the social class processes and forms of discrimination which generate inequalities. For some areas, such as the relationship between income inequality and mean population mortality, there is a need for a high quality systematic review. Primary research gaps also existing, for example on the impact of housing policy, availability and tenure. Conclusion: Politics, economics and public policy are important determinants of population health. Countries with social democratic regimes, higher public spending and lower income inequalities have populations with better health. There are substantial gaps in the synthesised evidence on the relationship between political economy and health and there is a need for higher quality reviews and empirical studies in this area. However, there is sufficient evidence in this review, if applied through policy and practice, to have marked beneficial health impacts.